(untitled) (Journal of the College of Basic Education, 2024)
A number of reasons have contributed to the exacerbation of the problem of drinking water pollution in the city of Baghdad, which has left negative effects on the health of the city’s residents who use water for drinking and cooking purposes and harshly for other domestic uses. The study aimed to identify the reasons for the exacerbation of the problem of water pollution in the Tigris River as well as to identify The nature of the pollutants that increase human diseases, and laboratory analyzes were conducted Some of the chemical and physical elements that cause contamination of drinking water for some water purification plants in the city of Baghdad, which amounted to (10) elements between the years (2018 and 2023) for the purpose of comparison between them. The results of the analyzes showed that all elements were high for the year 2023 compared to the year 2018, which indicates that Water pollution has increased, and this is an indication of the seriousness of the health situation accompanying it and affecting the health of the city’s residents, while all measures are being taken to reduce it.